(3GdeaGgje GdEOGQjI GdMOjKIs - (3jGSQ CMeO(B, (3YQHjGJs ((3YeGf(B:s (3OGQjGaG GdYdejI ddfTQ(B,s, 2008)
(3jVe GdcJGH GdeONd Edi Yde GdGOGQI , JWhQ GdacQ GdGOGQj hGdeOGQS GdGOGQjI , GdJNWjW hGJNGP GdbQGQGJ GdGOGQjI , GJNGP GdbQGQGJ GdGOGQjI , GdJfXje , GdSdWI hGdeSDhdjI , GdJhLjg hGdbjGOI , GdMhGaR , GdQbGHI(B. s
(3HjHdjhZQGajG(B: (3U(B. 233s
Keywords: (3GJNGP GdbQQGJs; (3GdGOGQIs; (3GdJNWjWs; (3GdQbGHI GdGOGQjIs